Avaliação nutricional do resíduo da semente do urucum e sua utilização em rações para frangos de crescimento lento contendo sorgo como principal fonte de energia - Souza, Davyd Herik (2014)
The objective this study was determine the chemical composition and the apparent metabolizable energy (EMA) and apparent corrected for nitrogen balance (EMAn) of the annatto seed by-product (RSU) and evaluate its use in rations for broiler growth slow formulated with sorghum as the main source of energy. To determine the EMA and EMAn two metabolism assays (14 to 21 and 28 to 35 days of age) were performed. Was used completely randomized design (DIC) in a 2x2 factorial design (two strains and two ages) with 5 replicates per treatment, 5 poultry in the first test and 4aves in the second. The EMA and EMAn values were not significantly influenced by the type of strain, however, suffered significant influence of age, obtaining higher values with older poultry. The RSU showed 88,77% dry matter, 4.083 kcal/kg of gross energy, 15,43% crude protein , 14,43% acid detergent fiber, 37,11% neutral detergent fiber and 1,86% ether extract. The values determined for EMA and EMAn in dry matter and EMAn in natural matter, were 2.462, 2.314 and 2.054 kcal / kg for poultry 14-21 days of age and 3.187, 3.174 and 2.817 kcal / kg for poultry from 28 to 35 days, respectively. In the performance trial, 420 chicks carijó pesadão lineage from 1 to 78 days of age in DIC in 2x7 factorial were housed, where the factors were 2 sexes and 7 rations, totaling 14 treatments. With 3 replicates of 10 poultry per treatment. The rations were: R1 - ration composed of corn and soybean meal; R2 - ration with 100% sorghum replacing corn without adding pigmentante, R3, R4, R5, R6 and R7 - ration with 100% sorghum replacing corn with the addition of 3, 6, 9, 12 and 15% of RSU, respectively. Regardless of gender, the diets did not affect the performance variables and carcass characteristics. However, the inclusion of RSU influenced color parameters of meat making it more pigmented. In poultry feed slow growing containing sorghum as the main energy source, can include up to 15% of RSU, because the level of inclusion of the residue did not influence performance and carcass characteristics of poultry, and you can reduce the problems of pigmentation of the meat with total replacement of corn by sorghum with inclusion of RSU starting 3%.